2003
DOI: 10.1007/s10350-004-7279-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Laparoscopic Surgery for Rectal Cancer in 101 Patients

Abstract: In terms of the intraoperative and early postoperative course, the laparoscopic resection of rectal cancer in a selected cohort of patients compares favorably with the open technique. Because follow-up time is limited to date, only very preliminary information can be given on tumor-related outcome data. However, these preliminary data appear to suggest that rectal cancer resection can be performed by laparoscopy in accordance with established principles of cancer therapy and that port-site metastases are not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
62
2
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(74 citation statements)
references
References 23 publications
6
62
2
4
Order By: Relevance
“…These include less pain, an earlier return of bowel function, a shorter duration of hospital stay, greater facilities to resume social activities, and a preservation of the abdominal wall [2]. Although experience of laparoscopic excision of rectal cancer has been reported [1,3,4,7,10,13,18,20,21] there is no evidence of the oncological safety of laparoscopic total mesorectal excision (TME) with sphincter preservation. Most studies reported high anterior resections, i.e., partial mesorectal excisions, and abdominoperineal excisions.…”
mentioning
confidence: 98%
“…These include less pain, an earlier return of bowel function, a shorter duration of hospital stay, greater facilities to resume social activities, and a preservation of the abdominal wall [2]. Although experience of laparoscopic excision of rectal cancer has been reported [1,3,4,7,10,13,18,20,21] there is no evidence of the oncological safety of laparoscopic total mesorectal excision (TME) with sphincter preservation. Most studies reported high anterior resections, i.e., partial mesorectal excisions, and abdominoperineal excisions.…”
mentioning
confidence: 98%
“…12 However, the quality of some studies remain debatable, particularly with scant information on the tumour size and location, technique and short follow-up periods. 13 Furthermore, it is difficult to know whether the tumours resected where particularly favourable to laparoscopy.…”
Section: Oncological Safetymentioning
confidence: 99%
“…Although the German and Austrian Laparoscopic Colorectal Surgery Study Group recently reported results from 380 patients undergoing laparoscopic proctectomy, follow up was short (24 months) [26]. In addition to the problems of small numbers and short follow up, some authors fail to perform time-to-event (actuarial, Kaplan-Meier) analysis of diseasefree survival and local pelvic recurrence, making any conclusions regarding oncologic outcome difficult [27]. Many series report results for select patients with early stage tumors, which is reasonable given the technical issues of laparoscopic manipulation of tumor, but which makes the data unhelpful with regard to deciding as to whether the technique is appropriate for all patients with rectal cancer.…”
Section: Oncologic Issuesmentioning
confidence: 97%
“…Unfortunately, there have been few reports of oncologic outcomes following laparoscopic proctectomy for rectal cancer [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. There have been only a handful of published series with greater than 50 patients and greater than 3 years follow up.…”
Section: Oncologic Issuesmentioning
confidence: 98%